A review of managed nitrate addition to enhance surface water quality. Issue 7 (2nd April 2016) - Beutel, Marc W.; Duvil, Ricardi; Cubas, Francisco J.; Matthews, David A.; Wilhelm, Frank M.; Grizzard, Thomas J.; Austin, David; Horne, Alexander J.; Gebremariam, Seyoum
Abstract: Nitrate is a significant water pollutant with potential environmental impacts ranging from eutrophication to health risks to infants. But under certain circumstances nitrate may enhance water quality through a number of mechanisms, including enhancing oxidant capacity, regulation of redox potential, and suppression of nitrogen-fixing cyanobacteria. In this review the authors explore a range of case studies in which nitrate addition enhanced surface water quality including: purposeful addition of nitrate salts to lakes to repress internal phosphorus (P) loading, enhance organic matter oxidation, or impede bottom-water accumulation of methylmercury; purposeful and incidental addition of nitrate from point and nonpoint discharges to reservoirs and lakes; nitrogen (N) addition to lakes to affect phytoplankton and zooplankton composition; and nitrate addition to estuary sediment to repress hydrogen sulfide production. Nitrate addition decreased internal P and methylmercury loading, repressed sulfide production, and enhanced surface water quality by lowering total P, chlorophyll content, and phytoplankton dominance by cyanobacteria. No case study reported a worsening of eutrophic conditions due to nitrate addition, and a number of studies reported near complete loss of nitrate from the systems to which it was added. When purposely adding nitrate to anoxic surface waters, protocols should be used to maximize nitrate loss via biological denitrification but minimize enhancement of phytoplankton productivity. These protocols should include adding nitrate close to the sediment-water interface to promote nitrate loss via denitrification, managing the timing and magnitude of nitrate addition so that nitrate is depleted prior lake overturn in the fall, and not adding nitrate to N-limited systems. Elimination of existing N discharges to receiving waters should be implemented on a case-by-case basis with the awareness that nitrate in discharges may enhance surface water quality, particularly by suppressing internal P loading and associated phytoplankton productivity. In addition, managers and regulators should look to couple existing nitrate discharges with hypoxic water bodies in an effort to sustainably enhance water quality while removing nitrate from aquatic ecosystems via biological denitrification.